Visualizing the quality of GNSS multivariate data - Vani, B.; Ivanova, Ivana; Monico, JFG; Shimabukuro, M. (2014)
This paper presents aspects related to the definition, management, and communication of data quality with application to a multivariate data set from Global Navigation Satellite System (GNSS). We stated about the quality in a context of scientific research with GNSS data presenting quality elements that can be applied to scientific research. A case study focusing on time varying quality elements is presented, where interactive data quality visualization schemes are applied to visualize positional accuracy and attribute accuracy varying on time, allowing the users to perform queries. We highlight the main features of the implemented visualizations and conclude with suggestions for future applications.